EFFECT OF ZNO NANO PARTICLES AGAINST STRAINS OF ESCHERICHIA COLI - Thangam, Anju; Ramlakshmi, Sakthi; Pritam, . (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â The antimicrobial activity of zinc oxide nano particles against E. coli strains was investigated as a model for gram-negative bacteria. Zinc oxide nanoparticles were prepared and characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and ultraviolet (UV) analysis. The antimicrobial study was performed by well diffusion assays and growth rate studies, with different concentrations of zinc oxide nano particles. The results showed zinc oxide nanoparticles to be an effective bactericide. Scanning electron microscopy was used to study the bactericidal action of these nano scale materials. The treated E. coli cells showed damages by formation of pitsâ€ in the cell wall of the bacteria, while the zinc oxide nanoparticles was found to be accumulated in the bacterial membrane. A membrane with such morphology exhibits a significant increase in permeability, resulting in death of the cell. Atomic force microscopy analysis of nanoparticle treated bacterial DNA showed changes in DNA. The results suggest that these nano materials, which can be prepared in a simple and cost-effective manner, may be suitable for the formulation of new types of bactericidal materials Keywords: Zinc oxide nano particles, Antimicrobial activity, Scanning electron microscopy.